Research on The Impact of Digital Inclusive Finance on County Economic Resilience in The Yangtze River Delta Region - Sheng, Junhui (Transactions on Economics, Business and Management Research, 2024)
This study investigates the varying impacts of digital inclusive finance's breadth, depth, and digitalization on county economic resilience using empirical analysis. The results highlight that digitalization significantly and positively influences economic resilience, underscoring the crucial role of digital technology in bolstering counties' risk resistance. Conversely, enhancements in breadth and depth do not exhibit a substantial positive effect, indicating that mere financial coverage or complexity are insufficient for directly augmenting resilience. Among the six dimensions of digital finance depth, investment and credit emerge as key drivers of economic resilience, confirming the importance of capital investment and credit management in fostering risk resistance. However, the promotion of payment and insurance may incur short-term adaptation costs. Consequently, policies should strike a balance between short-term adaptation and long-term development in advancing digital finance to ensure the steady progress of county economies.